ANALYSIS OF THE FINANCIAL FEASIBILITY OF THE LAYER DUCK (Anas sp) BREEDING BUSINESS IN SEUNEBOK BARU VILLAGE, MANYAK PAYED DISTRICT, ACEH TAMIANG - Zahra, Alvina; Basriwijaya, Kiagus M. Zain; Saragih, Faoeza Hafiz (Syarif Hidayatullah State Islamic University Jakarta, 2024)
This research aims to analyze the cost structure and profitability of the broiler duck farming business (Anas Sp) in Batee Puteh village, Langsa Lama sub-district, Langsa city. The method used is a survey method and direct interviews with breeders. The population in this study were breeders who cultivated broiler ducks with an ownership scale of more than 100 individuals, totaling 2 people. The method used in sampling is the Census Method, namely by taking the entire population to be used as a sample. The data collected includes primary data and secondary data. The research results show that the cost structure incurred by breeders consists of: fixed costs amounting to IDR 4.473.535,-/year with a percentage of 2,98% and variable costs as big as IDR 79,369,000/year with a percentage of 52,91%. The total income received by duck breeders in Batee Puteh Village is IDR151.200.000,-/year with total production costs of IDR83.842.535,-/year thereby generating huge profits IDR67.357.465,-/Year and IDR5.613.122,-/Month with the average profit being IDR33.678.733,-/Year and IDR2.806.561,-/Month. Based on the results of the sensitivity analysis under normal conditions and after changes in production, a 5% decrease in production, a 10% increase in feed prices and a 15% decrease in cage usage costs indicate that the duck farming business in Batee Puteh Village is still feasible to run.